MSMEs Focus on Instagram Account Quality : Key Factors to Prioritize in Instagram Posting - Berto Mulia Wibawa; Ninditya Nareswari (JURNAL SOSIAL HUMANIORA (JSH), 2019)
These days most of MSMEs have a quite good understanding of social media and how it works for their business. In Indonesia, Instagram is one of the best powerful tools to introduce and market their product instantly. However, social commerce face problems especially in customer trust. It is suspected by customer doubt to the key factors of social media online shop, i.e : reputation, transaction, communication, safety, information quality, economic feasibility, and word-of-mouth referrals. The purpose of this study is to test a framework of Instagram account quality model and its impact on MSMEs social media marketing strategy. An online-based questionnaire was administered to 271 MSMEs. Furthermore, structural equation modeling was used to analyze the data. Findings indicate that there are significant effect between information quality, reputation, safety, communication, and economic feasibility to the Instagram account quality construct. The practical implications emphasize on MSMEs first need to develop their information quality on Instagram, because that is the most significant factors towards Instagram account quality in online store perception.  A focus on improving information quality will also help MSMEs to communicate and promote their post to reach more audience and interaction with potential consumers.